QUALITY PROFILE OF SMOKED AFRICAN SHARPTOOTH CATFISH (CLARIAS GARIEPINUS) TREATED WITH UNCARIA GAMBIER (UNCARIA GAMBIR ROXB) - Sari, Selly Ratna; Agustini, Sri; Wijaya, Agus; Pambayun, Rindit (Jurnal Dinamika Penelitian Industri, 2017)
The purpose of this research was to study antibacterial properties of gambier on the quality charecteristic of smoked African sharptooth catfish (Clarias gariepinus)  which was marinated by  antibacterial gambier, and to review the effect of concentration and marination time of gambier on the physical, chemical and microbiology characteristic of smoked African sharptooth catfish. Research applied completely randomized design with the concentration of gambier and marination time as treatment with 3 replication.The concentration of gambier consist of A1 (0%), A2 (2%), A3 (4%) and A4 (6%). The marination time consist of  B1 (15 minute), B2 (30 minute) and B3 (45 minute). The parameters were Water activity (aw), Protein content, Texture, color (L*lightness, C*chroma and H*hue) and Total plate count (TPC). Test result showed that the   concentration  and marination time had significant effect on characteristic of smoked African sharptooth catfish. The characteristic of smoked African sharptooth catfish were: water activity (0.78-0.86), Protein content (30.57-33.47%), texture (717.6-835.2 gf), color L* (27.8-37.8), C* (4.1-6.3%), H*(21.8-34.2o), TPC (2.36-5.49 Log Cfu/g) and the best treatment was A4B3 (6% 45 m). All treatment showed the characteristic of smoked African sharptooth catfish which was introduced with gambier had better characteristic than control.